Langkah Strategi UMKM Menuju Bisnis Global: Studi Kasus Kopi Kenangan Cabang Jl. Pancing No. 184, Medan - M. Fikrie Fachrian Lubis; MHD. Haiqal Wijaya; Clara Citra Sinaga; Andhita Dean Vega; Dionisius Sihombing; Fadli Agus Triansyah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
This study aims to analyse the strategies implemented by Kopi Kenangan MSMEs, particularly the branch at Jl. Pancing No. 184 Medan, in facing the challenges of globalisation and penetrating the international market. The method used is a case study with a descriptive qualitative approach through interviews, observations, and documentation. The results of the study show that Kopi Kenangan is well prepared to compete in the global market through strengthening internal management, utilising digital technology, and building a brand image based on Indonesian coffee identity. The expansion strategies implemented include selecting markets with cultural proximity, adapting products to local preferences, and collaborating with international partners. The main obstacles faced include competition with global brands, differences in consumer tastes, financial constraints, and export regulations. However, business opportunities remain wide open in line with the increasing global coffee consumption trend, interest in authentic local products, and government support in promoting and facilitating MSMEs. This study concludes that the success of MSME internationalisation is largely determined by the synergy between internal company quality, digitalisation, partnership networks, and external support from the government.